Libyan Islamic Banks Experience in Reducing Bank Liquidity from an Islamic - zenbela, Hatem Abdurahman; Mohd, Mohd Abdul Wahab Fatoni; Lubis, Asmuliadi (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
Background: The problem with the study is that the problem of bank liquidity in Libyan Islamic banks is exacerbated by the excess of bank liquidity coverage. (2): Purpose: The study aims to learn about Libyan banks' experience in reducing bank liquidity from an Islamic perspective: Malaysian banks are a model. The study highlights the importance of highlighting Libyan Islamic banks' experience in reducing bank liquidity from the perspective of Islamic Malaysian banks as a model. (3) Method: The study followed a qualitative approach to evaluating internal and external factors, circumstances and variables associated with Libyan Islamic banks' experience in reducing bank liquidity from an Islamic perspective. Individual open interviews were conducted with employees of Libyan Islamic Banks, estimated at 15 employees from Libyan Islamic Banks. Fifteen questions were posed to participants, centered on internal control and its elements on bank liquidity and its components from an Islamic perspective. The study found several findings, (4) Results: including that bank liquidity risk is the risk to banks and may amount to a crisis related to the bank's lack of cash that enables it to fulfil its day-to-day duties to customers. And (5) Conclusion: include an attempt to adopt a peace model and to open the door to short, medium and long-term investments in order to maintain the levels and rates of bank liquidity of Libyan Islamic banks.